Buzzer versus water resistance phonation used in voice therapy. Results obtained with physical modeling. (April 2021) - Laukkanen, Anne-Maria; Horáček, Jaromír; Radolf, Vojtěch
Highlights: Voice therapy uses phonation, both through a mechanical buzzer (Shaker) and through a tube in water. Both methods interrupt airflow repeatedly and modify oral pressure and vocal fold vibration. This study used an experimental model, since the details of phonation in such tasks are difficult to study in humans. Poral, Psub, mean airflow rate, flow resistance, Ptrans, glottal area variation and lowest vocal tract resonance frequencies were measured. The Shaker offered less Poral oscillation, lower Ptrans, smaller maximum glottal amplitude and lower maximum closing velocity of the glottis. Abstract: Objective: Mechanical buzzers have been developed to clear excessive mucus from the lungs and trachea. Recently, they have been tested for voice therapy. By rapidly interrupting airflow they cause an oscillation of oral pressure, resembling phonation through a tube into water, which is traditionally used in voice therapy (water resistance therapy, WRT). This study compared phonation through a buzzer (Shaker deluxe™) with WRT with a glass resonance tube. Methods: Measurements were made for subglottic and oral air pressures, airflow, transglottic pressure ( Ptrans ) and peak-to-peak (p-t-p) oral pressure oscillation, and for glottal area variation, using a physical model of voice production, as such detailed study is not possible in humans. High-speed-imaging was used to study glottal area variation during phonation. Shaker was tested in both horizontal and upright positions. Results: Shaker upright had slightly higher flow resistance than resonance tube 10 cm in water, while Shaker horizontally had ca half of that. Ptrans was lower for Shaker in both positions, and maximum glottal amplitude and maximum glottal area declination rate were lower. Buzzing frequency for Shaker horizontally approximately corresponded to water bubbling frequency, while it was about twice that for Shaker upright. P-t-p oral pressure oscillation was higher in WRT, seemingly due to the much lower frequency of the lowest acoustic resonance of the vocal tract prolonged by the resonance tube. Conclusions: WRT may offer stronger 'massage-like' effect for the vocal tract and vocal folds than Shaker, while Shaker may promote softer phonation.